Time Series Data Analysis in Forecasting Educated Unemployment Rate in Aceh Province - Winny Dian Safitri; Muhammad Ikhwan; Nadlia Ariyati; Rajul Hakim (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2022)
Educated unemployment is the most important problem that must be solved by the government. Studies related to unemployment are very interesting to study. This study examines the relationship between educated unemployment in Aceh Province. The purpose of this study is to examine the modeling of educated unemployment in Aceh Province using secondary data. Forecasting was carried out to predict unemployment in Aceh Province in the period until 2030. The results of this study show that Aceh's educated unemployment rate continues to increase. The recommendations of this study are expected by the government to make improvements in various development sectors, especially programs that rely on improving human resources in order to change the labor recruitment system in Aceh Province to avoid a decrease in the unemployment rate in Aceh Province.